Immunological Aspects Involved in the Degeneration of Cryopreserved Arterial Allografts - González-Gay, Mario; López-Martínez, Rocío; Busto-Suárez, Sara; Riedemann-Wistuba, Mariel Estefanía; Menéndez-Herrero, María Ángeles; Álvarez-Marcos, Francisco; Alonso-Pérez, Manuel; Alonso-Arias, Rebeca (Frontiers in Surgery, 2020)
Introduction: Cryopreserved arterial allografts have remained an option in patients requiring distal revascularization or associated with vascular infection, in the absence of a valid autogenous saphenous vein. The objective of this study is to describe the different clinical, anatomopathological and immunological findings related to vascular transplant rejection. Methods: In a prospective trial, 35 patients who underwent cryopreserved allogeneic arterial bypass were studied, including demographics and conduit patency. Anti-HLA antibody production was stablished prior to the surgery, 7 days, 1 month, 3 months and every 3 months since. Clinical and ultrasound evaluation was added after the first month. Donor HLA-typing was retrieved whenever available, allowing for the characterization and quantification of donor specific antibodies. Cytotoxic crossmatch test was also performed. A second group of patients with allograft degenerations registered during the follow up period was studied. In this group, exclusively for aneurysm description and histopathological analysis, they were included those degenerated vascular transplants from the original series, but also those implanted prior to the beginning of the study and degraded during follow up. Results: All patients studied displayed an increase in anti-HLA antibodies one month after the intervention, regarding bypass patency. In total, 14 patients fulfilled requirements for the study of donor specific antibodies, equally showing IgG production detectable one month after surgery. The presence of complement-fixing antibodies was also confirmed. Antibody levels were not related to graft degeneration. No specific immune markers able to predict aneurysmal development and evolution were found. From the original group, 3 patients suffered aneurysmal degeneration during follow up, together with 9 bypasses previously implanted. Average time until the first degeneration was 33±19.7 months, with 30.6±17.7 and 54.5±2.5 months for a second and third degeneration, when occurring. Therefore, subsequent vascular transplants frequently augmented the time for new degenerations, despite increasing sensibilization. Samples from 8 degenerated allografts were available for analysis, unexpectedly showing inflammatory infiltrate in only 4 cases and immune complex deposition in 7. Conclusions: Immune response against vascular transplants was confirmed in all cases, but chronic rejection did not necessarily provoke bypass degradation or reduced the time for new aneurysms to develop in subsequent allografts.